2021
DOI: 10.22541/au.163872623.38837838/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The return of the RSV

Abstract: Respiratory syncytial virus (RSV) hospitalizations disappear in 2020. Now, with winter 2021 completely over in southern hemisphere, RSV has returned. Despite it is difficult to measure the impact of pandemic mitigation measures, it appears that the acute respiratory infections in pediatrics are returning to their usual epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The most accredited hypothesis to explain this uncommon finding was that the strict adoption of non-pharmaceutical interventions to contain SARS-CoV-2 diffusion (including handwashing and social distancing) also reduced the circulation of other infectious agents, such as RSV [ 71 ]. Unfortunately, this reduction was only transient, with subsequent rebound during the fall and winter seasons in 2021–2022 [ 72 , 73 , 74 ]. For example, a recently published French study reported a delayed RSV epidemic in the period usually corresponding to the end of the epidemic season [ 75 ].…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%
“…The most accredited hypothesis to explain this uncommon finding was that the strict adoption of non-pharmaceutical interventions to contain SARS-CoV-2 diffusion (including handwashing and social distancing) also reduced the circulation of other infectious agents, such as RSV [ 71 ]. Unfortunately, this reduction was only transient, with subsequent rebound during the fall and winter seasons in 2021–2022 [ 72 , 73 , 74 ]. For example, a recently published French study reported a delayed RSV epidemic in the period usually corresponding to the end of the epidemic season [ 75 ].…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%